KEBIJAKAN PENGEMBANGAN PEDAGANG PASAR CIGOMBONG KOTA JAYAPURA - Kadir , Akhmad; Wanggai, Lodewijk Luis; Saragi, Anwar (LPPM Uncen, 2024)
The aim of the community empowerment program which is related to the policy of developing the Cigombong traditional market as a traditional market in Jayapura City, is to increase the competitiveness of traditional Papuan people's traditional trade in Jayapura City. Traditional Markets, to encourage traditional markets to be able to compete and be competitive with modern shopping centers and shops requires professional management and empowerment of traditional markets. It is hoped that the results of the service will create an orderly, safe, clean and healthy traditional market. In another aspect, it can increase sales results, and traditional markets can act as a driving force for the regional economy.